Sustainability Today 2011
DOI: 10.2495/st110411
|View full text |Cite
|
Sign up to set email alerts
|

Removal of nickel from aqueous solutions using Saudi activated bentonite

Abstract: This research project investigates the application of Saudi activated clay (bentonite) to remove nickel from aqueous solutions. The removal characteristics of nickel ions from aqueous solution using Saudi activated bentonite were investigated under various operating variables like shaking time, solution pH, clay dosage and initial metal concentration. The results showed that the sorption of nickel ions on Saudi activated clay was relatively fast and the equilibrium was reached after 40 min. They also showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Saudi activated bentonite was used for the removal of lead and nickel from aqueous solutions. The results showed that using Saudi bentonite to remove heavy metals from aqueous solutions is promising process [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Saudi activated bentonite was used for the removal of lead and nickel from aqueous solutions. The results showed that using Saudi bentonite to remove heavy metals from aqueous solutions is promising process [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…The adsorption percentage increased with increasing pH and reached its highest values at approximately pH ≤ 8. Lower adsorption percentages were observed at lower pH values due to the formation of H + that covered the metal ions [ 42 , 43 , 44 ]. The PEI-AN and Fe/PEI-AN showed maximum adsorption efficiencies of at a pH ≤ 8 that were 83 and 91%, respectively.…”
Section: Resultsmentioning
confidence: 99%